Aggressive End-of-Life Care and Symptom Relief Treatments in Terminally Ill Patients Who Had Discussed Withdrawal of Mechanical Ventilation: A Hospital-Based Observational Study. (November 2020) - Chang, Hsiao-Ting; Lin, Ming-Hwai; Chen, Chun-Ku; Chen, Tzeng-Ji; Hwang, Shinn-Jang
Objective: The aim of this study was to explore the status of aggressive end-of-life care and symptom relief treatments in terminally ill patients who had discussed the withdrawal of mechanical ventilation. Methods: This research is a retrospective observational study based on a chart review. Terminal patients aged ≥20 years, who were intubated with mechanical ventilation support, who underwent hospice-shared care, and who personally, or whose close relatives, had discussed the withdrawal of mechanical ventilation with hospice-shared care team members in a tertiary hospital in Taiwan during 2012 to 2015 were included. Demographics, medical conditions, and aggressive end-of-life care, including hospitalization, use of vasopressors, artificial nutrition, tube feeding, antibiotics, and symptom relief treatments including the use of opioids, steroids, and sedatives, were identified. The modes of care and treatments of patients by the status of withdrawal of mechanical ventilation were compared. Results: A total of 141 patients had discussed the withdrawal of mechanical ventilation, and 111 (78.7%) had been withdrawn. Aggressive end-of-life care was noted in all patients regardless of mechanical ventilation status. There were no significant differences in the number and pattern of aggressive end-of-life care measures between patients who had or had not been withdrawn. There were significantly higher rates of symptom relief treatments used in patients who had been withdrawn. Conclusions: Aggressive end-of-life care is common for patients who have discussed the withdrawal of mechanical ventilation. There are significantly higher rates of symptom relief medications administered in patients who have been withdrawn from mechanical ventilation.